Gravitational waves in a magnetized plasma - Mofiz, U.A. (BRAC University, 2010)
An overview of gravitational wave and its possible detection while propagating in a plasma is given. The linear propagation of gravitational wave in magnetized plasma is considered. It is found that a × polarized gravitational wave excites Alfve′n modes while a + polarized wave excites magneto-acoustic waves propagating parallel to the gravitational wave. In merging binary pulsars gravitational wave energy can be converted into pulsar wind at a large scale.